MATHEMATICS IN CONTEXT: A LEARNING DESIGN FOR TEACHING NUMBER PATTERN IN JUNIOR HIGH SCHOOL - Iskandar, Ratu Sarah Fauziah (Prima: Jurnal Pendidikan Matematika, 2024)
This study aims to create an effective learning design for teaching number pattern concepts to 8th grade students using the Realistic Mathematics Education (RME) approach, while incorporating the context of Shio Tradition in Chinese Culture. The research employs a design research methodology consisting of three distinct stages: preliminary design, design experiment, and retrospective analysis. In the preliminary design stage, researchers analyze the current curriculum, student needs, and RME principles to develop initial instructional materials and strategies. These materials uniquely integrate the cyclical nature of of Shio Tradition in Chinese Culture as a culturally relevant context for exploring number patterns. The design experiment stage involves implementing these materials in real classroom settings, collecting data through observations, student work samples, and teacher feedback. Finally, the retrospective analysis stage evaluates the effectiveness of the learning design, identifying strengths, weaknesses, and areas for improvement. Throughout all stages, the study focuses on incorporating key RME principles, including the use of realistic contexts, student-constructed models, and interactive instruction. Throughout all stages, the study focuses on incorporating key RME principles, including the use of realistic contexts, student-constructed models, and interactive instruction. The resulting learning design is expected to enhance students' understanding of number patterns, improve their problem-solving skills, and increase their engagement with mathematics while also promoting cultural awareness. This research contributes to the growing body of knowledge on effective, culturally responsive mathematics instruction and provides a systematic approach to developing and refining RME-based learning designs for middle school mathematics education.